Pengaruh Healthcare Service Quality terhadap Kepercayaan (Trust) Melalui Kepuasan Pasien pada Puskesmas di Kabupaten Jember - Purwiningsih, Driana Desy; Ika Barokah Suryaningsih; Viera Wardhani (LPPM Hang Tuah Pekanbaru, 2023)
The decrease in the Community Satisfaction Index from 2018 to 2021 from 89% to 79% shows the dissatisfaction with services at the Public Health Center, so it is necessary to manage the improvement of service quality through behavioral attitudes, officer expertise, and process quality in providing services. The purpose of this study was to prove the effect of health service quality on trust through patient satisfaction at the Public Health Center in Jember Regency. The research was conducted through a survey using a questionnaire on 204 patients from 6 selected health centers with consecutive sampling techniques. Data analysis techniques using Structural Equation Model (SEM) with Partial Least Square (PLS). The results show that satisfaction is influenced by attitudes and behaviors and process quality, but not expertise. Attitude, behavior, and satisfaction have a direct effect on trust, while process quality has an indirect effect through satisfaction. Trust was not influenced by expertise. The attitude and behavior of health workers greatly affect satisfaction and trust, so officers at the Public Health Center must have good attitudes and behavior in serving patients.